2023
DOI: 10.3390/ijms24119445
|View full text |Cite
|
Sign up to set email alerts
|

Alpha2 Adrenergic Modulation of Spike-Wave Epilepsy: Experimental Study of Pro-Epileptic and Sedative Effects of Dexmedetomidine

Abstract: In the present report, we evaluated adrenergic mechanisms of generalized spike-wave epileptic discharges (SWDs), which are the encephalographic hallmarks of idiopathic generalized epilepsies. SWDs link to a hyper-synchronization in the thalamocortical neuronal activity. We unclosed some alpha2-adrenergic mechanisms of sedation and provocation of SWDs in rats with spontaneous spike-wave epilepsy (WAG/Rij and Wistar) and in control non-epileptic rats (NEW) of both sexes. Dexmedetomidine (Dex) was a highly select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The sedation sleep induced by DEX showed a character of deep sedation as explained previously. 24 Interestingly, the post‐sleep seizure had higher power in a delta frequency band (1–4 Hz) and attenuated power in 7‐Hz harmonics (14 and 21 Hz) than pre‐ and post‐injection seizures. Moreover, the attenuated power in beta frequencies might also indirectly indicate the dopaminergic release as stated and discussed in previous studies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The sedation sleep induced by DEX showed a character of deep sedation as explained previously. 24 Interestingly, the post‐sleep seizure had higher power in a delta frequency band (1–4 Hz) and attenuated power in 7‐Hz harmonics (14 and 21 Hz) than pre‐ and post‐injection seizures. Moreover, the attenuated power in beta frequencies might also indirectly indicate the dopaminergic release as stated and discussed in previous studies.…”
Section: Discussionmentioning
confidence: 91%
“… 21 In the literature, 1 to 5 times higher doses of ATI were used to recover DEX‐induced anesthesia or sedation 22 , 23 and DEX induces sedation above the doses of 3 μg and also induces high‐voltage spindles. 22 Although a study addressed that DEX can prolong SWDs via intraperitoneal route as well, 24 , 25 , 26 we picked the dose of 2.5 μg 1/5 of ATI dose as well as the doses slightly below the sedative doses in order to understand if DEX has an effect on the SWDs expressed in GAERS, as well as to antagonize ATI. In our previous study, as we established the SWD‐suppressing dose of ATI through intracerebroventricular (i.c.v.)…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports on dexmedetomidine increasing the duration of SWD activity ( 15 ) provide evidence that dexmedetomidine influences SWD duration. For instance, Sitnikova et al ( 47 , 48 ) provided preliminary results of dexmedetomidine increasing mean duration of SWDs in another model of genetic absence epilepsy Wistar Albino Glaxo/Rijswijk (WAG/Rij), and dexmedetomidine does not shorten the SWDs unlike other anesthetics ( 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, dexmedetomidine significantly reduced the number of c-Fos positive cells in the rat brain ( 66 ). However, another study demonstrated a pro-epileptic effect of dexmedetomidine in spike-wave epilepsy in WAG/Rij rats ( 84 ). In previous a study on the rat hippocampus, the α2-AR antagonist was implicated in the NE-mediated anti-epileptic effect in the CA3 domain ( 85 ).…”
Section: Effects Of α 2 -Adrenergic Receptors On E...mentioning
confidence: 99%